Religiosity and youth substance use in a Muslim context. Issue 3 (2nd July 2016) - Unlu, Ali; Sahin, Ismail
ABSTRACT: The literature shows that young people are more vulnerable than adults to substance use. Religiosity is one of the factors that has been considered to protect youth from substance use and has also been interpreted as contributing to the substance abuse recovery process. Conceptualizing religiosity as a multidimensional construct, this study aimed to investigate the influence of religiosity on substance use among youth. Three dimensions of religiosity—belief about religion, religious self-practice, and religious social environment—were examined as predictors of substance use. The survey data collected in 2010 by the Governance of Istanbul, Istanbul Department of Education, and Istanbul Police Department were used. Participants were high school students (n = 31, 272) between 14 and 18 years old. Structural equation modeling was used for statistical analysis and hypothesis testing. The study found a negative relationship between the three dimensions of religiosity and substance use. Religious social environment was found to be the strongest of the three dimensions. The findings suggest that religion has the potential to reduce the risk of substance use among youth. Implications for future research and policymakers were also discussed.